The Influence of Islamic Financial Literacy on Behavior and Decisions to Invest in Gold Instruments - Mahmud, Muhammad Daud bin; Sudirman, Muh. Sajjaj; Jufri, Fahria (Al-Tijary, 2024)
This study aims to investigate how gold investing decisions and behavior are affected by Islamic financial literacy. From a population of 31,119 people, 100 respondents from Morotai Island Regency in North Maluku Province were selected as the sample using the purposive sampling technique, with a 0.05 error tolerance. By testing the outer model and inner model, partial least square-structural equation modeling is applied as a data analysis tool. Only 2 of the 9 indicators used to measure the proposed Islamic financial literacy variable met the requirements. Both investment decisions and behavior variable indicators have 3 and 4 qualified indicators, respectively. Several previous studies have used a general measure of financial literacy, but this study measures financial literacy with a specific Islamic financial literacy scale. The results of this study prove that Islamic financial literacy has a positive influence on a person's behavior and his/her decision to invest using gold investment instruments. People who are well-literate in Islamic finance will have an impact on their investing behavior, which will allow them to make wise investment decisions and improve their financial well-being.